Novel kit for efficient extraction of long-segment genomic DNA by nanodisk adsorption - Wu, Siqi; Han, Zhaofang; Qiu, Hesong (Yayasan Ahmar Cendekia Indonesia, 2019)
The acquisition of complete DNA is usually the first and most critical step in many basic molecular biology applications. Isolation of complete total DNA from tissue samples is related to different physical and biochemical properties of tissue. Long fragments of DNA are easily degraded and fragmented, which poses a challenge for extracting complete long fragments of DNA. By comparing several different extraction methods and verifying the concentration and length of extracted DNA, it is proved that the kit we used has high efficacy. We provide tissue kit DNA extraction for long fragments and obtain long fragments of high purity DNA from almost any type of tissue, especially muscle and blood tissues.